Low gamma acrivity measurement of meteorites using HPGe-NaI detector system - COLOMBETTI, Paolo; TARICCO, Carla; Bhandari N.; Sinha N.; Di Martino M.; Cora A.; Vivaldo G. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2013)
The radioactivity in natural samples like cosmogenic isotopes in meteorites, in Moon samples, in earth and ice in Antarctica, produced by protons, neutrons, μ mesons and other charged particles, is very low, usually below 0.001 disintegration per minute per gram. Therefore, very special techniques are required, particularly if the sample cannot be destroyed for chemical separation and system must have possibility of counting large amount of sample. For this purpose we have developed a highly selective Ge–NaI coincidence spectrometer, operating in the underground Laboratory of Monte dei Cappuccini (INAF) in Torino. We have then improved it by developing a multiparametric acquisition system, which allows better selectivity of the coincidence windows (e.g., in meteorites, to disentangle cosmogenic 44Ti signal from overlapping 214Bi, originated by naturally occurring 238U). Applications of this system to the study of meteorites (chondrite, achondrite and iron samples) are described.